2012
DOI: 10.4111/kju.2012.53.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Nephrectomy on Postoperative Blood Pressure

Abstract: PurposeThe effects of partial nephrectomy (PN) on postoperative blood pressure (BP) are not known, and PN has the potential to worsen BP. We therefore sought to determine whether PN alters postoperative BP.Materials and MethodsPatients who underwent PN for suspected malignancy at our institution from 2002 to 2008 were included. Data on BP and medication from before and after PN were retrieved from family physicians. BP and number of antihypertensive medications were compared after surgery with preoperative val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Considering that partial nephrectomy (PN) can better preserve kidney function than radical nephrectomy (RN), PN is recommended to treat patients with early stage tumors ( 3 ). Nephrectomy-related HTN (NR-HT) has been reported by several studies, but robust high-level evidence is still needed ( 8 , 67 69 ). The use of targeted therapies, especially vascular endothelial growth factor signaling pathway (VSP) inhibitors, has remarkably increase the life expectancy of patients with mRCC while the increased risk of cardiovascular events turns out to be its obvious side effect ( 5 , 70 ).…”
Section: Treatment Of Rcc Cause Htnmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that partial nephrectomy (PN) can better preserve kidney function than radical nephrectomy (RN), PN is recommended to treat patients with early stage tumors ( 3 ). Nephrectomy-related HTN (NR-HT) has been reported by several studies, but robust high-level evidence is still needed ( 8 , 67 69 ). The use of targeted therapies, especially vascular endothelial growth factor signaling pathway (VSP) inhibitors, has remarkably increase the life expectancy of patients with mRCC while the increased risk of cardiovascular events turns out to be its obvious side effect ( 5 , 70 ).…”
Section: Treatment Of Rcc Cause Htnmentioning
confidence: 99%
“…In addition, vascular clamping in PN process could cause vasculitis and intimal hyperplasia, which would aggravate renal artery stenosis, resulting in the decline of glomerular capillary pressure and activated rennin-angiotensin system, leading to NR-HT ( 72 ). However, some studies drew opposite conclusions ( 67 , 73 ). A retrospective study involving 264 patients with PN showed that BP had no significant change after surgery ( 67 ).…”
Section: Treatment Of Rcc Cause Htnmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothetically, reduced blood flow and glomerular pressure in the partially resected kidney could cause renin release, ensuring the Goldblatt model of hypertension persists [35]. Several sporadic reports have indicated that PN [36,37] or nephrolithotomy [38] may precipitate postoperative hypertension and renal injury due to trauma can lead to postoperative hypertension in the form of "Page kidney" after repair [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, reduced blood flow and glomerular pressure in the partially resected kidney could cause renin release, ensuring the Goldblatt model of hypertension persists [35]. Several sporadic reports have indicated that PN [36,37] or nephrolithotomy [38] may precipitate postoperative hypertension and renal injury due to trauma can lead to postoperative hypertension in the form of "Page kidney" after repair [35]. Lawrentschuk and colleagues (2012) claimed that PN does not cause postoperative hypertension in 48 patients undergoing PN over 2 years [35], while Inoue and colleagues showed that hypertension progressed after PN (79 patients) compared with nephrectomy (24 patients) over 9 months [39].…”
Section: Discussionmentioning
confidence: 99%